Strategies of Management of the Garbage Housewives in the City of Pobè (Benin, West Africa): Diagnosis and Approaches of Solutions - ODOULAMI LIMA, LÉOCADIE (My University, 2017)
One of the difficulties that the population of Pobè feels is the one of the management of her garbage. This survey diagnoses the present fashions of management of the domestic garbage in the city of Pobè and propose some approaches of solutions. The documentary research, the investigations of land achieved by 256 households, completed by people list resources investigate, permitted to collect socioeconomic data, of the data on statistics on the pre-collection of the garbage,…. The results gotten after treatment of the data show that 46.06 % of the households incinerate garbage, 32.12 % bury them and 21.82 % reject them in the trash cans. Consequence, the populations cohabit with the garbage, inhale the odors descended of the putrefaction of garbage in spite of the orientations of the public hygiene code. This insalubrity is at the origin of the occurrence of 35 % of affections dermatological, of 43% of gastro-intestinal, of 13 % of febrile diarrhea, of 7 % of other illnesses diarrheic and 2% of cholera in the city of Pobè. It comes back to the local and state-controlled authorities with the involvement of the populations to experiment other strategies of management of garbage of the city of Pobè.
Keywords: Bénin; Pobè; management of the garbage; water illnesses